2012
DOI: 10.1615/critrevtherdrugcarriersyst.v29.i1.10
|View full text |Cite
|
Sign up to set email alerts
|

Scaffold: A Novel Carrier for Cell and Drug Delivery

Abstract: Scaffolds are implants or injects, which are used to deliver cells, drugs, and genes into the body. Different forms of polymeric scaffolds for cell/drug delivery are available: (1) a typical three-dimensional porous matrix, (2) a nanofibrous matrix, (3) a thermosensitive sol-gel transition hydrogel, and (4) a porous microsphere. A scaffold provides a suitable substrate for cell attachment, cell proliferation, differentiated function, and cell migration. Scaffold matrices can be used to achieve drug delivery wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
284
1
14

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 472 publications
(301 citation statements)
references
References 328 publications
(223 reference statements)
2
284
1
14
Order By: Relevance
“…The porous structure and tissue-like soft and wet properties of hydrogels have potential applications in the development of implantable drug reservoirs and cell scaffolds. [4][5][6][7] Moreover, hydrogels that are based on biomolecules, 8 such as proteins (e.g., collagen [Col] 9 and gelatin 10,11 ) and polysaccharides (e.g., hyaluronic acid 12,13 and chitosan 14,15 ), acquire not only excellent biocompatibility but also specific bioactivity from their building blocks. These features can artificially mimic the extracellular matrix (ECM) for cell growth and proliferation, 16 and are highly advantageous in tissue regenerative therapy.…”
Section: Introductionmentioning
confidence: 99%
“…The porous structure and tissue-like soft and wet properties of hydrogels have potential applications in the development of implantable drug reservoirs and cell scaffolds. [4][5][6][7] Moreover, hydrogels that are based on biomolecules, 8 such as proteins (e.g., collagen [Col] 9 and gelatin 10,11 ) and polysaccharides (e.g., hyaluronic acid 12,13 and chitosan 14,15 ), acquire not only excellent biocompatibility but also specific bioactivity from their building blocks. These features can artificially mimic the extracellular matrix (ECM) for cell growth and proliferation, 16 and are highly advantageous in tissue regenerative therapy.…”
Section: Introductionmentioning
confidence: 99%
“…A drug delivery system (DDS) represents a practically promising technology that can modify the biodistribution of drugs and consequently enhance efficacy. Therefore, there have been several investigations of drug delivery materials demonstrating their feasibility in drug therapy 13) . Some previous reports have shown that DDS technology is necessary to enhance the therapeutic efficacy of various drugs 9,14,15) .…”
Section: Introductionmentioning
confidence: 99%
“…In brief, receptor-mediated targeting system is the one that functioned with ligands via chemical coupling or physical coating ways, reaching the desired sites by the special interaction between the ligands in the system and the receptors on the surface of the desired organ Goyal et al, 2014b). There are many receptors present on the surface of hepatic cells, and receptor that is specific to hepatic parenchymal cells is asialoglycoprotein receptors, which has the ability to recognize the galactosylated ligands, lactobionic acid ligand, asialofetuin ligands, soybean-derived steryl glucoside ligands and many more (Garg et al, 2012;Malik et al, 2014). Similarly, glycyrrhetinic acid (GA) receptors are mainly found on the sinusoidal surface of mammalian hepatocytes.…”
Section: Introductionmentioning
confidence: 99%